A COMPARATIVE EVALUATION OF TWO DIFFERENT DOSES OF INTRATHECAL 1% 2-CHLOROPROCAINE WITH FENTANYL AS ADJUVANT FOR INFRUMBILICAL SURGERIES - Dr Jyoti Raina; Dr Madan Katoch; Dr Jyoti Khanna; Dr Anuradha Sen; Dr Chashamjot Bawa; Dr Mehak Dureja (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Intrathecal anesthesia is crucial for surgical procedures, providing effective analgesia and muscle relaxation. Among these agents, 2-chloroprocaine has gained popularity due to its rapid onset and shorter duration. This study aims to evaluate and compare the efficacy of two doses (40 mg and 50 mg) of 2-chloroprocaine in terms of analgesia, onset, duration, and anesthesia quality. Secondary objectives include investigating side effects associated with fentanyl and chloroprocaine use. Methods: This study was conducted at the Department of Anaesthesiology and Intensive Care, Government Medical College, Jammu, over a period of one year from November 2017 to October 2018. The enrolled patients were divided into two equal groups, with 30 patients in each group: Group A received intrathecal 1% 2-chloroprocaine (40 mg) with fentanyl (20 μg), while Group B received intrathecal 1% 2-chloroprocaine (50 mg) with fentanyl (20 μg). Results: Group B demonstrated a significantly earlier onset of sensory and motor block compared to Group A (p-value<0.001*). The time for two segmental regression of sensory block and the duration of sensory block were also significantly longer in Group B (p-value <0.001*). Furthermore, patients in Group B took a longer time to reach a modified Bromage scale of 0 for motor block. Both groups experienced bradyarrhythmias, hypotension, and nausea, but the differences were not statistically significant. Itching was observed in patients from both groups. However, there were no significant differences in hemodynamic parameters (heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and oxygen saturation) between the two groups. Conclusion: The amalgamation of intrathecal 1% 2-Chloroprocaine at a dose of 50mg alongside fentanyl at 20μg emerges as a compelling and captivating alternative in the realm of infraumbilical surgical interventions, surpassing the potency of chloroprocaine at 40 mg combined with fentanyl at 20μg.